INTERMEDIALITY IN THE AZERBAIJANI NOVEL: NOTES ON THE TOPIC - Osmanova Malahat Nasim (International Journal of Innovative Technologies in Social Science, 2024)
The article talks about intermediality, which determines the intertextual connection, based on the imagery of different types of art. Rauf Farhadov’s “Amorphia. Overdose” and Hafiz Mirza’s novels “The End and the Beginning” are studied at the level of problems of intermediality. The mentioned novels open against the background of musical works, clarifying the mutual referentiality of literature and music. The transformation of music into words is based on bringing different languages together in intermediality. All mentioned ideas are clearly manifested in the novels “Amorphia Overdose” and “The End and the Beginning”.